Efficient charge separation between Bi2MoO6 nanosheets and ZnO nanowires for enhanced photoelectrochemical properties. Issue 39 (21st September 2015) - Jin, Bingjun; Jiao, Zhengbo; Bi, Yingpu
Abstract : We demonstrate a facile and effective strategy for in situ growth of Bi2 MoO6 thin-nanosheets on well-aligned ZnO nanowires to construct novel hierarchical hetero-arrays, which exhibit excellent visible-light driven photoelectrochemical performances attributed to the efficient charge separation between Bi2 MoO6 and ZnO. Abstract : We demonstrate a facile and effective strategy for in situ growth of Bi2 MoO6 thin-nanosheets on well-aligned ZnO nanowires to construct novel hierarchical hetero-arrays, which exhibit excellent visible-light driven photoelectrochemical performances attributed to the highly efficient charge separation between Bi2 MoO6 nanosheets and ZnO nanowires.